2020
DOI: 10.1016/j.stem.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Stem Cell-Based Alveolospheres Provide Insights into SARS-CoV-2-Mediated Interferon Responses and Pneumocyte Dysfunction

Abstract: Coronavirus infection causes diffuse alveolar damage leading to acute respiratory distress syndrome. The absence of ex vivo models of human alveolar epithelium is hindering an understanding of COVID-19 pathogenesis. We report a feeder-free, scalable, chemically-defined, and modular alveolosphere culture system for propagation and differentiation of human alveolar type 2 cells/pneumocytes derived from primary lung tissue. Cultured pneumocytes express the SARS-CoV-2 receptor ACE2 and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
386
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(410 citation statements)
references
References 80 publications
21
386
0
3
Order By: Relevance
“…Our findings suggest that developing astrocytes are particularly vulnerable to SARS-CoV-2, however another recent study indicates that adult astrocytes may also be susceptible to infection and that other coronavirus receptors, like CD147, are abundant in mature astrocytes ( 11 , 30 ). We observe an increase in CD147 expression upon infection, suggesting a potential positive feedback loop, as observed in case of ACE2 in lung alveolosphere infection ( 34 ). Glial vulnerability to SARS-CoV-2 may extend across the lifetime but can be particularly consequential at early stages of brain development.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings suggest that developing astrocytes are particularly vulnerable to SARS-CoV-2, however another recent study indicates that adult astrocytes may also be susceptible to infection and that other coronavirus receptors, like CD147, are abundant in mature astrocytes ( 11 , 30 ). We observe an increase in CD147 expression upon infection, suggesting a potential positive feedback loop, as observed in case of ACE2 in lung alveolosphere infection ( 34 ). Glial vulnerability to SARS-CoV-2 may extend across the lifetime but can be particularly consequential at early stages of brain development.…”
Section: Discussionsupporting
confidence: 68%
“…ACE2 correlated genes in this cell population were enriched for regulators of the immune response ( Fig. 2e), with several of these genes found to be upregulated in alveolosphere cultures infected with SARS-CoV-2 36 . In addition to alterations in the cytokine microenvironment, changes in cellular immune populations were also identi ed in the COPD samples, dysregulation of several genes in in ammatory pathways (AREG, CCL3, CXCL8, SOCS1), and high levels of cytotoxic and exhaustion-related genes in CD4 and CD8 T Cells from COPD lungs.…”
Section: Discussionmentioning
confidence: 95%
“…1, Supplementary Table 3). SARS-CoV-2 utilizes the host ACE2, and other putative factors such as BSG, NRP1 and HSPA5, as entry receptor and TMPRSS2, CTSL or FURIN as priming proteases to facilitate cellular entry [33][34][35][36][37][38][39][40] . Consistent with prior reports analyzing normal lung tissue 33,34,41 , ACE2 and TMPRSS2 are expressed predominantly in epithelial cell types ( Fig.…”
Section: Expression Pro Le Of Sars-cov-2 Associated Receptors and Facmentioning
confidence: 99%
“…We also found that CTLVtotal was negatively correlated with absolute consolidation volume. A previous experimental study reported interferon-mediated inflammatory responses, loss of surfactant proteins, and apoptosis of pneumocytes in infected alveolospheres [ 20 ]. Histological studies have reported diffuse alveolar damage in patients with ARDS caused by SARS-CoV-2 [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%